Non-enzymatic and rapid detection of glucose on PVA-CuO thin film using ARDUINO UNO based capacitance measurement unit. - Dhiman, Tarun Kumar; Poddar, Mrinal; Lakshmi, G. B. V. S.; Kumar, Rahul; Solanki, Pratima R. (Biomedical Microdevices, 2021)
Glucose measurement is one of the essential health monitoring practices for maintaining blood sugar levels. Here, we have fabricated a highly specific capacitive nano-sensor for non-enzymatic glucose detection. Capacitance measurements were carried out on polyvinyl alcohol capped copper oxide (PVA-CuO) thin films on indium tin oxide (ITO) coated glass using ARDUINO UNO. The capacitance study shows a decrease in capacitance with an increase in glucose concentrations. The applicability in real samples was performed by studying the glucose in the presence of fetal bovine serum. Most commonly found interfering agents were used for interference studies, which confirmed the capacitive nano-sensor specificity. The system was further checked for repeatability up to six readings and reproducibility up to 5 chips. The shelf-life study showed stability for four weeks of a chip. These studies indicate that this capacitance-based measurement unit can be used for reliable, rapid, and non-enzymatic detection of glucose in real sample.